2018
DOI: 10.4088/jcp.17m11565
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythm Sleep-Wake Disorders Predict Shorter Time to Relapse of Mood Episodes in Euthymic Patients With Bipolar Disorder

Abstract: Comorbid CRSWD, mainly delayed sleep-wake phase disorder, could be a significant predictor of relapse in BD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…12 A recent study with a shorter duration (48 weeks) found a relationship between circadian dysfunction and shorter intercrisis period. 13 Although further research is necessary, strategies that contribute to circadian rhythm regulation may be able to improve the prognosis of BD patients.…”
Section: Discussionmentioning
confidence: 99%
“…12 A recent study with a shorter duration (48 weeks) found a relationship between circadian dysfunction and shorter intercrisis period. 13 Although further research is necessary, strategies that contribute to circadian rhythm regulation may be able to improve the prognosis of BD patients.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective cohort study of 104 euthymic patients with bipolar disorder reported that the comorbidity of circadian rhythm sleep-wake disorders, mainly delayed sleep-wake phase disorders, were significantly associated with the time to relapse of mood episodes. 25 In addition, our previous study revealed that a later timing of the circadian activity rhythm (10 consecutive hours with the highest amplitude values) was significantly associated with an increase in the depressive episode relapses. 9 Therefore, the present study supports these previous studies.…”
Section: Discussionmentioning
confidence: 92%
“…Interpersonal and social rhythm therapy, which addresses interpersonal problems and disrupted social rhythms, has been reported to be effective in the prevention of bipolar mood episodes 26 . Furthermore, the aforementioned prospective cohort study of patients with bipolar disorder reported that the comorbidity of circadian rhythm sleep–wake disorders, including irregular sleep–wake rhythm disorders, could be a significant predictor of relapse of mood episodes 25 . These previous studies and the present study suggest that the maintenance of consistency in day‐to‐day sleep/wake patterns might be useful as an adjunct therapy to prevent the recurrence or relapse of mood episodes in patients with bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in borderline personality disorder the prevalence of DSWPD is shown to be significantly higher than in the wider population [ 127 129 ]. However, the presence of circadian disorders has also been shown to predict earlier symptom relapse in bipolar disorder [ 130 ]. It remains difficult to distinguish which is the cause and which the effect and so psychiatric disorders should be considered a correlation which could be a potential cause.…”
Section: Preamblementioning
confidence: 99%